The Value of Life and Reproductive and Professional Autonomy - Frith, Lucy (Cambridge quarterly of healthcare ethics, 2025)
This article considers John Harris’ work on autonomy, specifically reproductive autonomy, outlined in The Value of Life and developed throughout his career. Harris often used the concept of reproductive autonomy to make the case for liberal approaches to developments in reproductive and genetic technologies. Harris argued that reproductive autonomy should be highly valued, and therefore we need compelling arguments to justify limiting it in anyway. When discussing reproductive autonomy, Harris focused mainly on restrictions on the potential users of reproductive technologies autonomy, that is, prospective parents. This article extends the discussion of autonomy and the appropriate limits to individuals exercising their autonomy to medical professionals working in this area. Given reproductive technologies have become part of routine medical practice, this article considers whether the current restrictions on both patients and clinicians, as imposed by regulators and professional guidelines, remain ethically justified.